Gender Interventions in the Dutch Police Force: Resistance as a Tool for Change?. Issue 3 (3rd July 2018) - van den Brink, Marieke; Benschop, Yvonne
ABSTRACT: Previous studies have documented strong resistance towards gender interventions. By contributing to theories on gender change, this paper increases our understanding of the reasons for this resistance and looks at how this resistance can be made productive in gendered interventions. Drawing on a case study in the Dutch Police force, the authors use case reconstructions of appointments to examine the introduction and reception of gender quota. They show how radical interventions such as quota can help to uncover the subtlety of gender inequality practices and make persistent and implicit stereotypes visible and discussable; they also show how radical interventions can trigger the reflexivity of actors. They conclude that the resistance against the interventions can be made productive because it allows for alternative construction of values. An analysis of resistance to gender interventions can contribute to diagnosing problems in the strategising and implementation of these interventions.